Isolated cerebral intraaxial varix. - Kelly, K J; Rockwell, B H; Raji, M R; Altschuler, E M; Martinez, A J (American Journal of Neuroradiology, 1995)
A case of isolated parenchymal venous varix not seen on angiography is reported. CT demonstrated a well-defined cystic lesion with peripheral enhancement deep within the left temporal lobe. MR demonstrated a high-signal-intensity lesion with hemosiderin rim.